Analysis of entropy generation in peristalsis of Williamson fluid in curved channel under radial magnetic field. (October 2019) - Nawaz, Sadaf; Hayat, Tasawar; Alsaedi, Ahmed
Highlights: Curvature and radial magnetic field effects are accounted. Modeling for Williamson fluid is done. Soret and Dufour aspected are considered. Velocity, thermal and slip conditions in peristalsis are employed. Entropy generation is studied. Abstract: The objective of present study is to analyze the peristaltic activity of Williamson fluid in curved configuration. Flow formulation is made by employing radial magnetic field and Soret and Dufour effects. Slip conditions for velocity, temperature and concentration are applied. Entropy analysis is also carried out. Modeling is given using lubrication approach. Stream function, velocity, temperature and concentration solutions have been derived. Effects of different parameters are analyzed on flow quantities of interest. Moreover streamlines are examined for different embedded parameters. Result reveals that Lorentz force tends to slow down the fluid velocity. The slip parameters for velocity and temperature lead to enhancement in corresponding profile whereas opposite behavior is noticed for concentration. Soret and Dufour effects lead to increase the temperature as well as entropy of the system. Complaint nature walls increase the fluid velocity for elastance parameters whereas damping nature reduces the fluid velocity.